Rwanda : Social and Economic Background Paper, and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
This paper provides information on the social and economic situation in Rwanda before and after the 1994 civil war. Important social and political developments in the period preceding the war are discussed. The far-reaching consequences of the 1994 civil war, together with the initial reconstruction efforts toward the end of that year, are described. The government's strategy for postwar reconstruction and rehabilitation is outlined, and the various efforts of the international community, including those of the IMF, in supporting Rwanda and the government's strategy are detailed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet